Efficacy of chitosan powder in reducing vaginal bleeding following a loop electrosurgical excision procedure: a randomized control trial - Güngördük, Kemal; Ünver, Hikmet Can; Şahin Uyar, Berican; Ergü, Berke Nur; Gülseren, Varol; Özdemir, İsa Aykut (My University, 2025)
Objective: To evaluate the efficacy of topical chitosan powder in reducing postoperative vaginal bleeding following a loop electrosurgical excision procedure (LEEP). Methods: In this randomized controlled trial, patients who underwent LEEP were randomly assigned (1:1) to the chitosan group, in which the wound area was sprayed with chitosan powder using a spray pump, or the control group. The primary outcome was the median quantity of vaginal blood lost in the early postoperative period (defined as within 6 h of the procedure). Results: The 124 women enrolled in the study were randomly divided into control (n = 61) and chitosan (n = 63) groups. The median amount of vaginal blood loss during the early postoperative period was significantly lower in the chitosan group than in the control group (198.85 [64.4–388.57] mL vs. 250.60 [67.7–552.87] mL; P < 0.001). The rate of late postoperative bleeding requiring hemostatic intervention was also lower in the chitosan group than in the control group (3.2% vs. 16.4%; P = 0.013). Superior cervical wound healing in the chitosan group compared to the control group was also observed. Conclusion: The application of chitosan powder to the cervical wound bed can improve surgical outcomes by decreasing post-LEEP vaginal bleeding and facilitating the healing of cervical wounds.
Keywords: Chitosan; Loop Electrosurgical Excision Procedure; Vaginal Bleeding